The Electronic Documents System and the efficiency of the staff of Ta Phraya Subdistrict Municipality, Ta Phraya District, Sa Kaeo Province - krajangmol, Umaphon (Journal of Modern business administration and management for Sustainable Development, 2024)
Abstract This research article aimed to study 1) To study the efficiency of the Electronic Documents System of the officer Ta Phraya District, Sa Kaeo Province. 2) To study the factors affecting the efficiency of the Electronic Documents System based on demographic characteristics of the officer Ta Phraya District, Sa Kaeo Province. The samples used in this research consisting is officer Ta Phraya District, Sa Kaeo Province a total of 120 people, who were operating electronic documents at the Ta Phraya District, Sa Kaeo Province. The instrument used in the research was a closed-ended questionnaire. The statistics approaches used in analysing data are descriptive statistics, percent, frequency, mean, standard deviation. The results of the research showed that demographic characteristic has no impacts on efficiency in work. But the Electronic Document System, affects the work performance of Ta Phraya District, Sa Kaeo Province staff. In terms of suitability,work process and also problems with statistical significance at the level of 0.05 Keywords: Efficiency, Documents Work , Electronic Document System, Ta Phraya Subdistrict Municipality